PENGARUH COLLATERAL ASSET, ASSET GROWTH, LEVERAGE, DAN PROFITABILITY TERHADAP DIVIDEND POLICY - Caroline Christie Wijaya; Yuniarwati Yuniarwati (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to examine and analyze the effect of collateral asset, asset growth, leverage, and profitability on dividend policy. 46 samples of manufacturing companies were selected in this study, with a total sample data of 138 manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019.This study uses the purposive sampling method in taking samples based on predetermined criteria. Multiple regression analysis technique was used in the data processing of this study and processed using the EViews version 12 program. This study shows that profitability has a significant and positive effect on dividend policy, while collateral asset, asset growth, and leverage have no significant effect on dividend policy. This study implies that the company's management must be able to maximize the available funds both to increase profitability and develop the company's operations to create a stable and increasing dividend distribution.